Acute small fiber neuropathy after Oxford-AstraZeneca ChAdOx1-S vaccination: A report of three cases and review of the literature - Abbott, MG; Allawi, Z; Hofer, M; Ansorge, O; Brady, S; Fadic, R; Torres, G; Knight, R; Calvo, M; Bennett, DLH; Themistocleous, AC (Wiley, 2022)
Introduction Small fiber neuropathy usually presents with gradual and progressive chronic length-dependent pain. Acute small fiber neuropathy is rarely reported. Three patients with acute onset neuropathic pain after Oxford-AstraZeneca ChAdOx1-S vaccination are described.